Clinical observation of a complete clinical, radiological and pathomorphological response in a patient with locally advanced gastric adenocarcinoma after neoadjuvant therapy - Diana Yu. Mironova; Vitaliy Yu. Skoropad; Tatev A. Agababyan; Natalya K. Silanteva; Ekaterina S. Zhavoronkova; Sergey A. Ivanov; Andrey D. Kaprin (LLC "MEDIAFORMAT", 2024)
Stomach cancer is an aggressive disease and represents a global health problem. Currently, more than 50% of patients with a newly diagnosed stomach cancer have a locally advanced process that requires a combined approach - a combination of surgical treatment and neoadjuvant/perioperative therapy. In a number of patients, after neoadjuvant therapy, there is a marked or even complete regression of the tumor; the prognosis of the disease, as well as the need for adjuvant therapy in this category of patients is the subject of discussion. This paper demonstrates the clinical observation of a complete clinical, radiological and morphological response after neoadjuvant therapy (2 cycles of chemotherapy FLOT + chemoradiotherapy), as well as long-term relapse-free survival in a patient with locally advanced gastric cancer.